Managing Oil Palm Plantations More Sustainably: Large-Scale Experiments Within the Biodiversity and Ecosystem Function in Tropical Agriculture (BEFTA) Programme - Luke, Sarah H.; Advento, Andreas Dwi; Aryawan, Anak Agung Ketut; Adhy, Dwi Nugroho; Ashton-Butt, Adham; Barclay, Holly; Dewi, Jassica Prajna; Drewer, Julia; Dumbrell, Alex J.; Edi,; Eycott, Amy E.; Harianja, Martina F.; et al. (Frontiers in Forests and Global Change, 2020)
Conversion of tropical forest to agriculture results in reduced habitat heterogeneity, and associated declines in biodiversity and ecosystem functions. Management strategies to increase biodiversity in agricultural landscapes have therefore often focused on increasing habitat complexity; however, the large-scale, long-term ecological experiments that are needed to test the effects of these strategies are rare in tropical systems. Oil palm (Elaeis guineensis Jacq.)—one of the most widespread and important tropical crops—offers substantial potential for developing wildlife-friendly management strategies because of its long rotation cycles and tree-like structure. Although there is awareness of the need to increase sustainability, practical options for how best to manage oil palm plantations, for benefits to both the environment and crop productivity, have received little research attention. In this paper we introduce the Biodiversity and Ecosystem Function in Tropical Agriculture (BEFTA) Programme: a long-term research collaboration between academia and industry in Sumatra, Indonesia. The BEFTA Programme aims to better understand the oil palm agroecosystem and test sustainability strategies. We hypothesise that adjustments to oil palm management could increase structural complexity, stabilize microclimate, and reduce reliance on chemical inputs, thereby helping to improve levels of biodiversity and ecosystem functions. The Programme has established four major components: (1) assessing variability within the plantation under business-as-usual conditions; (2) the BEFTA Understory Vegetation Project, which tests the effects of varying herbicide regimes; (3) the Riparian Ecosystem Restoration in Tropical Agriculture (RERTA) Project, which tests strategies for restoring riparian habitat; and (4) support for additional collaborative projects within the Programme landscape. Across all projects, we are measuring environmental conditions, biodiversity, and ecosystem functions. We also measure oil palm yield and production costs, in order to assess whether suggested sustainability strategies are feasible from an agronomic perspective. Early results show that oil palm plantation habitat is more variable than might be expected from a monoculture crop, and that everyday vegetation management decisions have significant impacts on habitat structure. The BEFTA Programme highlights the value of large-scale collaborative projects for understanding tropical agricultural systems, and offers a highly valuable experimental set-up for improving our understanding of practices to manage oil palm more sustainably.